MURIN: Multimodal Retinal Imaging and Navigated-laser-delivery for dynamic and longitudinal tracking of photodamage in murine models - Rico-Jimenez, Jose J.; Jovanovic, Joel; Nolen, Stephanie L.; Malone, Joseph D.; Rao, Gopikrishna M.; Levine, Edward M.; Tao, Yuankai K. (Frontiers in Ophthalmology, 2023)
Introduction Laser-induced photodamage is a robust method for investigating retinal pathologies in small animals. However, aiming of the photocoagulation laser is often limited by manual alignment and lacks real-time feedback on lesion location and severity. Here, we demonstrate MURIN: MUltimodal Retinal Imaging and Navigated-laser-delivery, a multimodality OCT and SLO ophthalmic imaging system with an image-guided scanning laser lesioning module optimized for the murine retina. The proposed system enables targeting of focal and extended area lesions under OCT guidance to benefit visualization of photodamage response and the precision and repeatability of laser lesion models of retinal injury. Methods MURIN optics were optimized for simultaneous near-infrared and visible wavelength imaging/laser lesioning. Custom LabView control software was developed to steer the photocoagulation laser and automatically deliver laser pulses to targets-of-interest. In vivo retinal imaging was performed in transgenic Müller glia-tdTomato reporter mice (Rlbp1:CreER; Rosaai14, 5 animals, 10 eyes) and microglia-GFP/Müller glia-tdTomato reporter mice (Cx3cr1GFP; Rlbp1:CreER; Rosaai14, 9 animals, 15 eyes) to visualize cellular changes in the retina after laser lesion delivery. Results Real-time MURIN imaging concurrent with laser lesioning allowed us to visualize lesion formation dynamics and any corresponding changes in retinal morphology. We observe increasing fluorescence photoconversion on SLO and scattering contrast on OCT. Significant morphological changes are visible on MURIN after high-severity photodamage. OCT cross-sections show the spatial extent of the lesions contract over time from diffusion areas of increased scattering to granular scatterers and corresponding SLO images show a radial pattern surrounding severe focal lesions, which may be a result of a change in Müller cell shape or orientation in response to injury. The inner plexiform layer is distorted and increased RPE thickness and scattering are observed, all of which are confirmed on corresponding hematoxylin and eosin (H&E) histology and differential interference contrast (DIC) microscopy. Discussion MURIN as a unique imaging platform that enables combined SLO and OCT imaging with an integrated image-guided laser lesioning module. This technology has clear benefits over existing multimodal imaging and laser lesioning systems by enabling simultaneous multimodal imaging, independent and precise control of Iridex laser pulse parameters and patterns, and real-time OCT and SLO visualization of lesion formation.